2022
DOI: 10.3389/fpsyg.2021.766827
|View full text |Cite
|
Sign up to set email alerts
|

Night Eating Syndrome in Patients With Obesity and Binge Eating Disorder: A Systematic Review

Abstract: Night eating syndrome (NES) is currently classified as an Other Specified Feeding or Eating Disorder (OSFED) under the Diagnostic Statistical Manual−5 (DSM-5). This systematic review aims to consolidate the studies that describe the sociodemographic, clinical and psychological features of NES in a population of patients with eating disorders (ED), obesity, or those undergoing bariatric surgery, and were published after the publication of the DSM-5. A further aim was to compare, where possible, NES with BED on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…For example, de Zwaan et al [ 7 ] found that across studies, the prevalence of NES in pre-operative bariatric patients ranged from 6 to 64% [ 7 ]. In attempt to elucidate the prevalence of NES using only the DSM-5 diagnostic criteria, Kaur et al [ 8 ••] reviewed the most up-to-date empirical literature, concluding that the overall prevalence of NES ranged from 2.8 to 8.2% across eating disorder, obesity, and bariatric surgery populations. Further, Kaur et al noted that when the cut-off score on the Night Eating Questionnaire (NEQ) (an assessment tool detailed in the assessment section) was decreased from 30 to 25, the prevalence of NES within these clinical populations increased (6.9 to 15.2%) [ 8 ••].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, de Zwaan et al [ 7 ] found that across studies, the prevalence of NES in pre-operative bariatric patients ranged from 6 to 64% [ 7 ]. In attempt to elucidate the prevalence of NES using only the DSM-5 diagnostic criteria, Kaur et al [ 8 ••] reviewed the most up-to-date empirical literature, concluding that the overall prevalence of NES ranged from 2.8 to 8.2% across eating disorder, obesity, and bariatric surgery populations. Further, Kaur et al noted that when the cut-off score on the Night Eating Questionnaire (NEQ) (an assessment tool detailed in the assessment section) was decreased from 30 to 25, the prevalence of NES within these clinical populations increased (6.9 to 15.2%) [ 8 ••].…”
Section: Overviewmentioning
confidence: 99%
“…In attempt to elucidate the prevalence of NES using only the DSM-5 diagnostic criteria, Kaur et al [ 8 ••] reviewed the most up-to-date empirical literature, concluding that the overall prevalence of NES ranged from 2.8 to 8.2% across eating disorder, obesity, and bariatric surgery populations. Further, Kaur et al noted that when the cut-off score on the Night Eating Questionnaire (NEQ) (an assessment tool detailed in the assessment section) was decreased from 30 to 25, the prevalence of NES within these clinical populations increased (6.9 to 15.2%) [ 8 ••]. These findings underscore the increased frequency of NES across clinical populations, suggesting some populations may be more vulnerable to developing NES.…”
Section: Overviewmentioning
confidence: 99%
“…Before and after bariatric surgery, eating behavior plays a crucial role in postoperative outcomes [4,5]. Eating disorders and problematic eating behavior, which are more common in bariatric surgery patients compared to the non-obese population, may have adverse effects on post-op bariatric surgery outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent eating disorders among the patients who are candidates for bariatric surgery can be listed as; binge eating disorder, night eating syndrome, emotional eating, and frequent snacking or grazing during the day. Moreover, although it has not yet been included in the DSM-5 (Diagnostic and Statistical Manual of Mental Disorders-5), food addiction also appears in studies carried out [6,8,9]. The literature indicates that binge eating disorder is observed in 4-45%, grazing in 20-60%, night eating syndrome in 42%, emotional eating in 38-59%, and food addiction in 36.8% of bariatric surgery candidates [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation